Non-invasive vagus nerve stimulation for PREVention and Acute treatment of chronic cluster headache (PREVA): A randomised controlled study. (May 2016) - Gaul, Charly; Diener, Hans-Christoph; Silver, Nicholas; Magis, Delphine; Reuter, Uwe; Andersson, Annelie; Liebler, Eric J; Straube, Andreas
Background: Chronic cluster headache (CH) is a debilitating disorder for which few well-controlled studies demonstrate effectiveness of available therapies. Non-invasive vagus nerve stimulation (nVNS) was examined as adjunctive prophylactic treatment of chronic CH. Methods: PREVA was a prospective, open-label, randomised study that compared adjunctive prophylactic nVNS ( n = 48) with standard of care (SoC) alone (control ( n = 49)). A two-week baseline phase was followed by a four-week randomised phase (SoC plus nVNS vs control) and a four-week extension phase (SoC plus nVNS). The primary end point was the reduction in the mean number of CH attacks per week. Response rate, abortive medication use and safety/tolerability were also assessed. Results: During the randomised phase, individuals in the intent-to-treat population treated with SoC plus nVNS ( n = 45) had a significantly greater reduction in the number of attacks per week vs controls ( n = 48) (−5.9 vs −2.1, respectively) for a mean therapeutic gain of 3.9 fewer attacks per week (95% CI: 0.5, 7.2; p = 0.02). Higher ≥50% response rates were also observed with SoC plus nVNS (40% (18/45)) vs controls (8.3% (4/48); p < 0.001). No serious treatment-related adverse events occurred. Conclusion: Adjunctive prophylactic nVNS is a well-tolerated novel treatment for chronic CH, offering clinical benefits beyond those with SoC.